Le Conseil économique et l’impact régional de la politique commerciale - Sinclair, A. (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractGiven that there are a number of possible models of the regional impact of a tariff, one would have hoped that the Council would have attempted to test the standard ones and/or to have developed new and better ones. After almost forty years Mackintosh's model is still probably the most persuasive model of the long run impact of the tariff in Canada. The Council in its main report has been largely content to repeat and to some extent to confuse elements of the conventional wisdom on the subject. Interesting points have been made in some of the background studies, particularly, among the studies reviewed, by Postner and by Dauphin.At a general level, the Council has failed to integrate its recommendations concerning tariff policy into the general framework of regional policy in this country. Specifically, the Council fails to consider explicitly that on "second best" grounds the elimination of tariffs may not lead to an improvement in resource allocation, nor does it consider in any detail policies which would be preferable to tariffs to achieve regional (and other) objectives which require intervention by the government. For a study which suggests that free trade would bring gains of at least five per cent of GNP, or over $8 billion per year at current levels of production, it would be unfortunate if a certain naïveté in exposition of the free trade case were to consign the document to the political dust-bin.